2020
DOI: 10.1016/j.ebiom.2020.103067
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding motif protein 10 suppresses lung cancer progression by controlling alternative splicing of eukaryotic translation initiation factor 4H

Abstract: Background RNA splicing defects are emerging molecular hallmarks of cancer. The gene encoding splicing factor RNA binding motif protein 10 (RBM10) has been found frequently mutated in various types of cancer, particularly lung adenocarcinoma (LUAD), but how RBM10 affects cancer pathogenesis remains to be determined. Moreover, the functional roles and clinical significance of RBM10 mutation-associated splicing events in LUAD are largely unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…In addition, our previous study showed that mutations in the gene encoding the splicing factor RNA‐binding motif protein 10 ( RBM10 ) were the hallmark of SSN tumorigenesis 29 . Another study reported that RBM10 mutations in LUAD generally lead to the loss of function and cause extensive alterations 32 . Consistent with these results, we found that the RNA splicing program was enriched in both components, suggesting that the high expression of genes related to RNA splicing contributes to tumour growth in GG and solid components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous study showed that mutations in the gene encoding the splicing factor RNA‐binding motif protein 10 ( RBM10 ) were the hallmark of SSN tumorigenesis 29 . Another study reported that RBM10 mutations in LUAD generally lead to the loss of function and cause extensive alterations 32 . Consistent with these results, we found that the RNA splicing program was enriched in both components, suggesting that the high expression of genes related to RNA splicing contributes to tumour growth in GG and solid components.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA binding motif protein 10 (RBM10) is a novel putative drug target. It is an auxiliary splicing factor that promotes exon skipping by binding to the adjacent intronic regions [ 37 ]. RBM10 was very recently found to be the second most frequently mutated gene, compared to commonly mutated tumor suppressor genes in LUAD patients.…”
Section: Lung Cancermentioning
confidence: 99%
“…RBM10 was very recently found to be the second most frequently mutated gene, compared to commonly mutated tumor suppressor genes in LUAD patients. RBM10 mutations co-occurred with major oncogenes EGFR and KRAS mutations in 93% and 78% of cases, respectively [ 37 ]. These mutations were suggested to have a role in driving LUAD development and progression, and are prevalent in female and younger non-smoking patients, highlighting RBM10 clinical significance.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…RBM10 is an RNA-binding protein and a splicing regulator located on the X chromosome, which is involved in pre-mRNA (messenger RNA) splicing and post-transcriptional regulation (14). Previous studies have confirmed that RBM10 could suppress disease progression and cell proliferation in LUAD via regulating the alternative splicing of NUMB and EIF4H (15,16). Moreover, Zhao et al verified that loss-of-function mutations in RBM10 contributed to the pathogenesis of LUAD (17).…”
Section: Introductionmentioning
confidence: 99%